2017
DOI: 10.1186/s13071-017-2284-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal transmission of Schistosoma haematobium infection among school-aged children in Kaedi town, southern Mauritania

Abstract: BackgroundMauritania is at the fringe of transmission of human schistosomiasis, which mainly occurs in the southern and southeastern parts of the country. This study aimed to assess the influence of rainfall seasonality on the prevalence of Schistosoma haematobium infection among school-aged children in Kaedi, southern Mauritania.MethodsCross-sectional surveys (i.e. parasitological, malacological and observations on water-related human activities) were carried out in Kaedi between September 2014 and May 2015, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 34 publications
4
19
2
Order By: Relevance
“…Thirty-one African countries including Sudan have the great burden of this disease, and millions of individuals have been suffering from schistosomiasis [ 3 ]. Africa houses at least 90% of infected people requiring schistosomiasis treatment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one African countries including Sudan have the great burden of this disease, and millions of individuals have been suffering from schistosomiasis [ 3 ]. Africa houses at least 90% of infected people requiring schistosomiasis treatment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates findings of Houmsou [21] in Nigeria, who reported no monthly or seasonal difference in the prevalence of infection. On the contrary, well-marked seasonal variation in Schistosoma infection was reported by several authors [16,17,[54][55][56]. The absence of seasonal difference in the occurrence in infection may suggest perennial transmission of infection noting high dependency of the population on stream water source.…”
Section: Discussionmentioning
confidence: 85%
“…Satellite temperature and precipitation products are suitable in providing useful information to understand and model the relationship between meteorological conditions and Schistosoma prevalence [9]. In recent years, a number of studies have indicated that S. haematobium infection exhibits seasonal variation [15][16][17] and that infection may vary between countries and even between regions in the same country. In some areas, the prevalence of S. haematobium is higher in the dry season [17][18][19], while in other areas, it is higher during the rainy season [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed B. pfeifferi has been shown to prefer solid supports (such as wood and leaves) and bedrock to sand and gravel [41]. Moreover there are accounts of the preference of the intermediate hosts for plastic waste [63], although no quantification of this preference exists to our knowledge. In this perspective a limitation of this study was to not have done specific trials to determine the degree of randomness obtained using our procedure for the random positioning of sampling quadrats, in particular the effect of the repositioning of the quadrat if it didn't land within the predefined distance to the shoreline with respect to the snail species' substratum preferences.…”
Section: Discussionmentioning
confidence: 97%